Fiber-based multiple access timing signal synchronization technique - 袁一博 王波 高超 王力军 (Chinese physics B, 2017)
A fiber-based,multiple access timing signal synchronization scheme is demonstrated.By coupling out the bidirectional transmission signals,a highly stable timing signal can be recovered at arbitrary points along the fiber with the help of the loop delay message broadcasted via ethernet from the local module.The experiment is carried out on a 30-km fiber placed in a temperature-controlled box.In one-day period,when the round trip fiber transfer delay fluctuation is60 ns,the fluctuations of the stabilized timing signal from the download and the remote modules were only ±125 ps and±100 ps,respectively.Also,the system error caused by transmission path asymmetry and thermal drift is calibrated,and a100-ps magnitude synchronization accuracy is realized.This method could provide new insights into the construction of a fiber-based time transfer network.